1991
DOI: 10.1002/ptr.2650050406
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of diuretic drug plants. 1. Phytochemical screening and pharmacological evaluation of Anethum graveolens L., Apium graveolens L., Daucus carota L. and Eruca sativa mill

Abstract: A preliminary phytochemical screening of fruits of Anethum gruveolens L., Apium gruveolens L., Daucus curotu L., and seeds of Erucu sutiuu Mill., revealed the presence of volatile oil, sterols andlor triterpenes, carbohydrates and/or glycosides, tannins and flavonoids in the four entitled plants; Glucosinolates were detected only in Erucu seeds. Pharmacological evaluation of the aforementioned plants for diuretic activity has shown the ethanolic extracts of Erucu sutiua seeds and fruits of Anethum gruueolens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Qualitative phytochemical analysis showed the presence of alkaloids, flavonoids, tannins, saponins and cardiac glycosides and the data for their quantitative determination has been presented (Table 5 ). Presence of tested secondary metabolites in the seeds of A. graveolens is in line with earlier reports [ 30 , 31 ]. The phytoconstituents detected in the plant materials could be responsible for their antimicrobial activity though their exact mode of action is poorly understood.…”
Section: Resultssupporting
confidence: 92%
“…Qualitative phytochemical analysis showed the presence of alkaloids, flavonoids, tannins, saponins and cardiac glycosides and the data for their quantitative determination has been presented (Table 5 ). Presence of tested secondary metabolites in the seeds of A. graveolens is in line with earlier reports [ 30 , 31 ]. The phytoconstituents detected in the plant materials could be responsible for their antimicrobial activity though their exact mode of action is poorly understood.…”
Section: Resultssupporting
confidence: 92%
“…Dill seed essential oil is used in perfumery to aromatize cosmetics, detergents, soaps, as carminative and for control of flatulence, colic, and hiccups in infants and children (Slupski, Lisiewska, & Kmiecik, 2005). Earlier, various pharmacological effects of dill seed essential oil such as anticancer (Zheng, Kenney, & Lam, 1992), antidiabetic (Panda, 2008), antisecretory (Hosseinzadeh, Karimi, & Ameri, 2002), cytotoxic to human lymphocytes (Lazutka, Mierauskiene, Slapsyte, & Dedonyte, 2001), diuretic (Mahran et al, 1992), antihyperlipidaemic (Yazdanparast & Alavi, 2001), and antihypercholesterolaemic activity (Tian, Ban, Zeng, Huang, & Wang, 2011) have been reported.…”
Section: )mentioning
confidence: 99%
“…However, in another study, dill powder and its essential oils have shown hypolipidaemic activity in rats, suggesting its possible use as a cardio protective agent 18 . Dill has also been reported as anticancer 19 , antidiabetic 16 , anti oxidant [20][21][22] , anti secretary 13 , antispasmodic 24 , cytotoxic to human lymphocytes 25 , insecticidal [26][27][28] , and diuretic 29 . In a study female rats were used to assess the effect of A. graveolens on female reproductive system, it has been found that dill can be used as a regulatory agent of the menstrual cycle 30 .…”
Section: Anethum Graveolens L Therapeutic Uses and Spasmolytic Activmentioning
confidence: 99%